1984
DOI: 10.1002/j.1552-4604.1984.tb02776.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lipid Effects of Antihypertensive Therapy: A Double‐Blind Comparison of the Effects of Methyldopa and Propranolol

Abstract: Thirty-two middle-aged men with essential hypertension completed a double-blind randomly allocated comparison of the effects of methyldopa versus propranolol on blood lipid levels. After a four-week period on a placebo for each drug, subjects were titrated for the next six weeks with either methyldopa from 500 to 2000 mg/day or propranolol from 80 to 320 mg/day plus a placebo for the other drug until supine diastolic blood pressure was below 90 mm Hg or the ceiling dose was reached. Subjects were then maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…However, some investigators [4] have reported that antihypertensives could not reduce mortality due to ischemic heart disease. It has been shown [5][6][7] that the administration of thiazide diuretics or certain [3-blockers causes abnormalities of glucose and lipid metabolism, especially an increase in triglyceride levels or a decrease in the concentration of high-density lipoprotein (HDL) cholesterol. These unfavorable effects of antihypertensive agents may contribute to the limited improvement seen in the incidence of ischemic heart disease despite adequate control of blood pressure.…”
mentioning
confidence: 99%
“…However, some investigators [4] have reported that antihypertensives could not reduce mortality due to ischemic heart disease. It has been shown [5][6][7] that the administration of thiazide diuretics or certain [3-blockers causes abnormalities of glucose and lipid metabolism, especially an increase in triglyceride levels or a decrease in the concentration of high-density lipoprotein (HDL) cholesterol. These unfavorable effects of antihypertensive agents may contribute to the limited improvement seen in the incidence of ischemic heart disease despite adequate control of blood pressure.…”
mentioning
confidence: 99%
“…Although total cholesterol and low‐density lipoprotein‐cholesterol (LDL‐C) were not different during pregnancy, women with previous pre‐eclampsia had higher levels of both total cholesterol and LDL‐C at both post‐partum visits. The raised triglyceride levels in pre‐eclampsia prior to delivery are unlikely to have been affected by the use antihypertensive agents, because alpha methyl dopa was most commonly used to treat hypertension and has been reported not to affect triglyceride levels 17 . During post‐partum follow up, none of the women was treated with antihypertensive agents and differences in post‐partum lipid levels were independent of whether the women were lactating.…”
Section: Alterations In Blood Lipids In Women With Pre‐eclampsiamentioning
confidence: 97%
“…The raised triglyceride levels in pre-eclampsia prior to delivery are unlikely to have been affected by the use antihypertensive agents, because alpha methyl dopa was most commonly used to treat hypertension and has been reported not to affect triglyceride levels. 17 During post-partum follow up, none of the women was treated with antihypertensive agents and differences in post-partum lipid levels were independent of whether the women were lactating. These results suggest that hypertriglyceridaemia may be a constitutional characteristic of women prone to develop pre-eclampsia and part of a more generalized dyslipidaemia that may be due to their elevated BMI.…”
Section: Alterations In Blood Lipids In Women With Pre-eclampsiamentioning
confidence: 99%
“…Η φαρµακευτική αγωγή, αν και µπορεί να περιορίσει ή να µειώσει σηµαντικά την υπέρταση, δεν µπορεί παρόλα αυτά να µειώσει τον κίνδυνο ενός καρδιακού επεισοδίου (Cooper, Hardy, Labarthe, Hawkins, Smith & Blaufox 1988, Farnett, Mulrow, Linn, Lucey & Tuley, 1991. Επιπρόσθετα, τα αντιυπερτασικά φάρµακα έχουν υψηλό κόστος, παρουσιάζουν αρκετές παρενέργειες και αυξάνουν άλλους παράγοντες επικινδυνότητας για καρδιοπάθειες (Ames & Hill 1976, Bielmann & Leduc 1979, Bloomgarden, Ginsberg-Fellner, Rayfield, Bookman & Brown 1984, Leon et al 1984. Για τους λόγους αυτούς, ο ρόλος της άσκησης κατά της υπέρτασης, ως πρωτεύουσα αγωγή, έχει αναγνωριστεί επαρκώς εδώ και πολύ καιρό (Blair, Goodyear, Gibbons & Copper 1984, Kannel et al 1972 Hackam et al 2010, Pescatello et al 2015, Sharman et al 2015, Hansen et al 2017, Pagonas et al 2017.…”
Section: συµπέρασµαunclassified